Rumusan Karakter Kerja Keras Dan Mandiri (Analisis Isi Video Kick Andy Episode Anak-Anak Pejuang Untuk Mendapatkan Pendidikan Yang Layak Guna Pembelajaran Pendidikan Pancasila Dan Kewarganegaraan) - Mami, Pita, Dra. Sundari S.H., M. Hum (2015)
This research is to describe the formula of hard work and independent character on the analysis of Kick Andy video, episode of anak-anakpejuang to acquire a better education for civic education learning. Data collection technique used in this research is documentation method and library study. This research is using content analysis method to understand the formula of hard work and independent character on the analysis of Kick Andy video. This is based on the content analysis data by drawing conclusion of a sign that describes message of hard work and independent character for civic education learning. This research can be concluded that in the Kick Andy video shows the struggle of children of the nation to acquire better education. Formula of hard work and independent character is narrated on the story of Papua, East Nusa Tenggara, and a girl who have to work hard so that she was able to continue her study into college. They struggle to achieve their dreams to meet success. In Kick Andy video it is expected that students will be motivated with the struggle of children of the nation for better education. Kick Andy video is not only can be used as civic education learning but also can be used as teachers' reference as hard work and independent formula on this content analysis in Kick Andy video episode of anak-anakpejuang to achieve a better education for civic education learning. Keywords: hard work character, independent character, analysis of Kick Andy video.